Implementation of Islamic Religious Education Values in the Tiban Tradition in Hargomulyo Village, Sekampung District, East Lampung Regency (International Journal of Education and Literature, 2025)
This study aims to identify Islamic educational values implemented in the Tiban tradition in Hargomulyo Village, Sekampung District, East Lampung Regency. Tiban is a rain-seeking ritual performed by the community during prolonged drought as a form of endeavor that combines elements of local culture with Islamic values. Using an ethnographic approach with qualitative methods, this research involved participatory observation, in-depth interviews, and documentation. The results show that the Tiban tradition in Hargomulyo Village implements Islamic educational values, including: (1) faith values, in the form of belief in Allah's power as the creator and regulator of the universe including rain; (2) worship values, reflected in the series of prayers, dhikr, and istisqa prayers accompanying the ritual; (3) moral values, in the form of tawakkal, patience, sincerity, and mutual cooperation in ritual implementation; and (4) social values, in the form of strengthening social cohesion and solidarity among residents. The transformation of this ritual demonstrates the acculturation process between Javanese culture and Islamic teachings that has developed harmoniously, although there are some elements that still need adjustment to be more in line with Islamic law. This research contributes to the preservation of local wisdom that aligns with Islamic values and the development of culture-based Islamic education.